Financial Technology (Fintech) Adoption and Marketing Innovation: Strategies for Enhancing Competitive Advantage of SMEs in the Digital Era - Yuttama, Faizal Rizky; Salsabela, Riska Nadiya (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat 2025, 2025)
This study aims to analyze the effect of financial technology (fintech) adoption and marketing innovation on the competitive advantage of Small and Medium Enterprises (SMEs) in Banyumas Regency. The background of this research lies in the challenges faced by SMEs in the digital era, particularly limited access to financing, inadequate financial recording, and the dominance of conventional marketing strategies. This research employed a quantitative approach using a survey method involving 120 SME owners selected through purposive sampling. Data were collected using a Likert-scale questionnaire (1–5). The data were analyzed with SPSS software through validity and reliability tests, multiple linear regression analysis, and classical assumption tests. The findings reveal that (1) fintech adoption has a positive and significant effect on the competitive advantage of SMEs, (2) marketing innovation has a positive and significant effect on competitive advantage, and (3) fintech adoption positively affects marketing innovation, which in turn strengthens its indirect effect on competitive advantage. These results confirm that the integration of fintech-based financial management with digital marketing strategies enhances operational efficiency, broadens market reach, and strengthens the competitive position of SMEs in Banyumas. The study recommends improving digital literacy and providing local government policy support to accelerate fintech adoption and encourage marketing innovation for SMEs in the digital era.